ASPECT OF THE NOTARIAL FUNCTION (Heritage, 2021)
The notary public service is a special public profession that has a specific role not only to establish legal security but also to strengthen the existing one. The Law on Notary Public opted for the so-called Latin type of notary because it was a natural ways of the historical roots of the Austro-Hungarian monarchy in our area. In step with this reform project, the necessary changes in civil and procedural law were entered. The concept of notary public was to be implemented in the entire civil law system. One of the reasons for the introduction of the institute of the notary public was to make courts more effective in the matter in which this is possible. Our legal system has joined many European legal systems which, in order to respect the principles of procedural economics and speed up the provision of legal protection in civil court proceedings, provide for the possibility of entrusting the conduct of court proceedings to a notary public. The notary public acts like a judge when working on probate, but his position is not completely equal to that of a judge, therefore, the competent court has the obligation to supervise the work of the notary public. The court may at any time ask the notary public to submit the case file to him and to submit a written report on his work.
Keywords: notary public, probate proceedings, impartiality of notaries, Serbia